Predominance of single bacterial cells in composting bioaerosols. (April 2015) - Galès, Amandine; Bru-Adan, Valérie; Godon, Jean-Jacques; Delabre, Karine; Catala, Philippe; Ponthieux, Arnaud; Chevallier, Michel; Birot, Emmanuel; Steyer, Jean-Philippe; Wéry, Nathalie
Abstract: Bioaerosols emitted from composting plants have become an issue because of their potential harmful impact on public or workers' health. Accurate knowledge of the particle-size distribution in bioaerosols emitted from open-air composting facilities during operational activity is a requirement for improved modeling of air dispersal. In order to investigate the aerodynamic diameter of bacteria in composting bioaerosols this study used an Electrical Low Pressure Impactor for sampling and quantitative real-time PCR for quantification. Quantitative PCR results show that the size of bacteria peaked between 0.95 μm and 2.4 μm and that the geometric mean diameter of the bacteria was 1.3 μm. In addition, total microbial cells were counted by flow cytometry and revealed that these qPCR results corresponded to single whole bacteria. Finally, the enumeration of cultivable thermophilic microorganisms allowed us to set the upper size limit for fragments at an aerodynamic diameter of ∼0.3 μm. Particle-size distributions of microbial groups previously used to monitor composting bioaerosols were also investigated. In collected the bioaerosols, the aerodynamic diameter of the actinomycetes Saccharopolyspora rectivirgula- and-relatives and also of the fungus Aspergillus fumigatus, appeared to be consistent with a majority of individual cells. Together, this study provides the first culture-independent data on particle-size distribution of composting bioaerosols and reveals that airborne single bacteria were emitted predominantly from open-air composting facilities. Highlights: Composting bioaerosols were collected by an Electrical Low Pressure Impactor. Bioaerosols analyzed by combining culture, flow cytometry and qPCR. Single bacteria were predominant in composting bioaerosols. Predominance of single cells is relevant in terms of dispersal.